Association of serum klotho level with albuminuria in middle‑aged and elderly participants without diabetes mellitus: a cross‑sectional study - Dawei Chen; Mengxing Chen; Zhixiang Qi; Yumei Tang; Xin Wan (BMC Nephrology)
Abstract Background The relationship between serum klotho level and albuminuria is unknown in middle-aged and elderly participants without diabetes mellitus (DM). Therefore, we will investigate the association between serum klotho level and albuminuria in middle-aged and elderly participants without DM. Methods Participants (aged 40–79) were from the five continuous cycles (2007–2016) of the National Health and Nutrition Examination Survey (NHANES). Multiple logistic regression was performed to investigate the association between serum klotho level and albuminuria. Results 9217 participants were included in the present study. 47.6% of the participants were male. The average age of the overall participants was 56.3 years (40–79 years). Overall, 823 participants with albuminuria were identified. After adjusted confounders (age, gender, marital status, ethnicity, family income to poverty ratio, education, body mass index, smoke, charlson comorbidity index, hypertension, hyperlipidemia, angiotensin converting enzyme inhibitor/angiotonin receptor blocker, and estimated glomerular filtration rate), participants with a high serum klotho level had a decreased risk for albuminuria. Compared with the lowest serum klotho level (Tertile 1), participants in Tertile 2 (odds ratio [OR] 0.83, 95% CI 0.70–0.99, P = 0.044) and Tertile 3 (OR 0.76, 95% CI 0.63–0.91, P = 0.003) had a lower risk of albuminuria (P for trend = 0.002). The stratified analysis showed that serum klotho level was still negatively associated with albuminuria in the subgroups, and statistically significant interactions were not observed in the subgroups (all P values for interactions > 0.05, except for the hypertension subgroup). Conclusions In middle-aged and elderly participants without DM, a high serum klotho level is associated with a decreased risk of albuminuria. In the future, the mechanism of the interaction between klotho and albuminuria needs to be elucidated to find new treatment targets for individuals without DM who suffer from albuminuria.